"Can You Hear Me Now?" Race, Motherhood, and the Politics of Being Heard. Issue 4 (December 2019) - Killen, Kimberly
Abstract: Motherhood as a political identity grants women political legitimacy, enabling them to make rights-based claims. However, the efficacy and possibility of motherhood as a political identity is entangled in the sexist and racist narratives that are inextricable from white supremacy. In this article, I analyze the language used by the Mothers of the Movement (MothM) at the 2016 Democratic National Convention to demonstrate how the identities and experiences of Black women, specifically Black mothers, are co-opted and reproduced as deficient, criminal, and irrelevant, thereby limiting their ability to make claims as mothers and citizens. How, then, can marginalized mothers confront the tools of white supremacy, which portray them as "bad" mothers and "bad" citizens, to be heard within the dominant order without conforming to it? I contend that in appropriating the very discourses and spaces that seek to exclude and subjugate them, the MothM demonstrate the hypocrisy of the system of "good motherhood"—all the while reaffirming their status as equal citizens deserving of political recognition. Drawing from Black feminist thinkers, I demonstrate how motherhood and the rights that the MothM claim as mothers can be conceptualized as assertions of freedom and equal citizenship.